2022
DOI: 10.1002/advs.202103735
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer Assisted Fast X‐ray Detection in Direct/Indirect Hybrid Perovskite Wafer

Abstract: Metal halide perovskite scintillators encounter unprecedented opportunities in indirect ionizing radiation detection due to their high quantum yields. However, the long scintillation lifetime of microseconds upon irradiation, known as the afterglow phenomenon, obviously limits their fast development. Here, a new type of hybrid X-ray detector wafer combining direct methylamine lead iodide (MAPbI 3 ) semiconductor and indirect zero-dimensional cesium copper iodide (Cs 3 Cu 2 I 5 ) scintillator through low-cost f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…[182] In addition, Liu et al reported a new hybridwafer X-ray detector that combines the direct-type MAPbI 3 and the indirect-type 0D Cs 3 Cu 2 I 5 luminescent body through a lowcost rapid tablet pressing process (Figure 27d-f). [183] Because of the rapid energy transfer between Cs 3 Cu 2 I 5 and MAPbI 3 , the response speed of the device to X-rays is greatly shortened by ≈30 times, reaching 36.6 ns, so that the large-area detector array has the capability of fast X-ray detection within 1 s. In addition, Cs 3 Cu 2 I 5 occurs at the grain boundary of MAPbI 3 blocking the path of ion migration, so that the detection limit of this Xray detector is 1.5× smaller than that of the direct-type MAPbI 3 and 10× lower than that of the indirect-type Cs 3 Cu 2 I 5 scintillator. The direct/indirect hybrid wafers also show higher operational stability in the environment without packaging.…”
Section: Combination Of Hp Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…[182] In addition, Liu et al reported a new hybridwafer X-ray detector that combines the direct-type MAPbI 3 and the indirect-type 0D Cs 3 Cu 2 I 5 luminescent body through a lowcost rapid tablet pressing process (Figure 27d-f). [183] Because of the rapid energy transfer between Cs 3 Cu 2 I 5 and MAPbI 3 , the response speed of the device to X-rays is greatly shortened by ≈30 times, reaching 36.6 ns, so that the large-area detector array has the capability of fast X-ray detection within 1 s. In addition, Cs 3 Cu 2 I 5 occurs at the grain boundary of MAPbI 3 blocking the path of ion migration, so that the detection limit of this Xray detector is 1.5× smaller than that of the direct-type MAPbI 3 and 10× lower than that of the indirect-type Cs 3 Cu 2 I 5 scintillator. The direct/indirect hybrid wafers also show higher operational stability in the environment without packaging.…”
Section: Combination Of Hp Materialsmentioning
confidence: 99%
“…Reproduced with permission. [183] Copyright 2022, John Wiley and Sons. benefits including 1D crystal structure, the congruent-melting feature, and the highly matching to spectral response of some universal photodetectors, such material shows high application potential in light-emitting devices.…”
Section: Perovskite Sc Scintillatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PL lifetime of 961 ns is comparable to the reported values of single crystals obtained through the solution method. 31,34 Based on the obtained crystals with good crystalline quality, we explored the total ionizing dose effect of gamma rays on Cs 3 Cu 2 I 5 single crystals. A 60 Co gamma-ray source with an average energy of 1.25 MeV was used.…”
mentioning
confidence: 99%
“…In the last decade, 3D metal halide perovskites (PVKs), with ABX 3 general formula (where A is a mono valent organic or inorganic cation, such as FA + (formamidinium), MA + (methylam monium) or Cs + (cesium), B is a metal cation, such as Pb 2+ or Sn 2+ , and X is an halogen) (Figure 1a), have emerged as one of the most promising families of mate rials for applications in various fields such as lasers, light emitting diodes, photode tectors, scintillation, and photovoltaic solar cells. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] This material family exhibits excellent optoelectronic properties, tun able bandgap, long charge carrier lifetime, lowcost and mildtemperature solution processability. [16] To date, perovskite solar cells (PSCs) have achieved record effi ciency of over 25%.…”
mentioning
confidence: 99%